European mothers' time with children : differences and similarities across nine countries - Jutta M. Joesch; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
We use data from the 1996 wave of the European Community Household Panel to present and compare the weekly number of hours mothers of children less than 16 years of age reported looking after children in nine European countries in 1996. In addition, we explore to what extent cross-country differences in socio-demographic characteristics and parents' employment status contribute to differences in maternal time with children across the nine countries. We find cross-country differences in the mean of the amount of time mothers reported looking after children. Only a small portion of these differences is explained by differences in socio-demographic characteristics and employment status across countries in Europe. For three country pairs, we use a Oaxaca decomposition to investigate whether behaviour differences or differences in sample characteristics explain more of the observed differences in mothers' time looking after children. According to our results, the differences between Ireland and the UK can be explained mainly by behaviour differences. The results for Germany vs. Austria and Denmark vs. Greece, however, depend on the weights used.
Keywords: J2; D1; 330; Frauenerwerbstätigkeit; Kinderbetreuung; Zeitbudgetforschung; EU-Staaten